Towards dsRNA‐integrated protection of medical Cannabis crops: considering human safety, recent‐ and developing RNAi methods, and research inroads. Issue 4 (23rd December 2022) - Willow, Jonathan; Silva, Ana I.; Taning, Clauvis Nji Tizi; Smagghe, Guy; Veromann, Eve
Abstract: Owing to the expanding industry of medical Cannabis, we discuss recent milestones in RNA interference (RNAi)‐based crop protection research and development that are transferable to medical Cannabis cultivation. Recent and prospective increases in pest pressure in both indoor and outdoor Cannabis production systems, and the need for effective nonchemical pest control technologies (particularly crucial in the context of cultivating plants for medical purposes), are discussed. We support the idea that developing RNAi tactics towards protection of medical Cannabis could play a major role in maximizing success in this continuously expanding industry. However, there remain critical knowledge gaps, especially with regard to RNA pesticide biosafety from a human toxicological viewpoint, as a result of the medical context of Cannabis product use. Furthermore, efforts are needed to optimize transformation and micropropagation of Cannabis plants, examine cutting edge RNAi techniques for various Cannabis –pest scenarios, and investigate the combined application of RNAi‐ and biological control tactics in medical Cannabis cultivation. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The need for nonchemical protection of medical Cannabis makes necessary the research development of RNA interference (RNAi) tactics to protect this expanding industry. The most critical aspect to support future applications is with regard to dsRNA pesticide biosafety from a human toxicological viewpoint.